The Effect of Leadership Style and Career Development on Turnover Intention among Employees in a Public Hospital - Muhammad Bintang Gadesya Putra; Kiki Sudiana (Greenation International Journal of Economics and Accounting, 2026)
Employee turnover still remains kind of a persistent issue in healthcare, partly because it messes with workforce stability , service quality, and also overall organizational performance. A lot of prior work looked at how leadership, or career development maybe, relates to keeping employees, but not much has really examined how those two aspects work together inside public healthcare organizations. In this specific research, the aim is to examine how Leadership Style and Career Development influence Turnover Intention among staff in a public hospital. A quantitative method was implemented, and survey data was gathered from 92 employees through purposive sampling, indicating it was not random. Subsequently, the data was analyzed using multiple linear regression. In summary, the findings indicate that both Leadership Style and Career Development have meaningful negative impacts on Turnover Intention, suggesting that greater values in these areas correspond with a reduced desire to quit. Among the two variables, Career Development emerged as the stronger predictor, indicating that employees place considerable importance on opportunities for professional growth and career advancement. The results also confirm that Leadership Style and Career Development jointly influence Turnover Intention. Moreover, the model accounts for 24% of the differences in Turnover Intention, indicating that there are probably additional organizational and personal factors as well, which affect employees' decisions on leaving. These results emphasize the significance of strong leadership and well-organized career advancement programs as essential approaches for enhancing employee retention within public healthcare institutions.